2017
DOI: 10.1002/nau.23444
|View full text |Cite
|
Sign up to set email alerts
|

A re‐adjustable sling for female recurrent stress incontinence and intrinsic sphincteric deficiency: Long‐term results in 205 patients using the Remeex sling system

Abstract: The Remeex re-adjustable sling provides a good cure rate for rSUI and ISD at long-term follow-up. The complications rate is acceptable since most complications are clavien II. The ability to re-adjust the sling tension during the follow-up allowed us to achieve cure for recurrence after the initial procedure, and to relieve obstruction in every case attempted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
(25 reference statements)
3
16
1
Order By: Relevance
“…In addition, 80.0% of patients were very satisfied or satisfied with the operation results at the 1-year follow-up. In addition, recent published research results are summarized in Table 4 [19202122232425]. In the current study, the short-term results of 70 patients with SUI (64 cases of SUI due to ISD and 6 recurrent SUI cases) who underwent REMEEX surgery revealed a subjective cure rate of 92.9% and an objective cure rate of 100%.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, 80.0% of patients were very satisfied or satisfied with the operation results at the 1-year follow-up. In addition, recent published research results are summarized in Table 4 [19202122232425]. In the current study, the short-term results of 70 patients with SUI (64 cases of SUI due to ISD and 6 recurrent SUI cases) who underwent REMEEX surgery revealed a subjective cure rate of 92.9% and an objective cure rate of 100%.…”
Section: Discussionmentioning
confidence: 53%
“…According to our department's clinical practice, all patients underwent urodynamic evaluation after the surgery. As some patients required sling tension readjustment during follow‐up, 8 postoperative urodynamics were performed once the last regulation had been done and after the final continence status had been achieved. Both pre‐ and postoperative urodynamic tests were performed and reported according to the International Continence Society (ICS) recommendations 14 .…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Several studies have demonstrated the usefulness of the Remeex® readjustable sling in rSUI [4][5][6][7][8] and ISD. [4][5][6][7][8][9] Outcomes of this procedure have previously been reported by our group, showing good results in terms of continence, with a low complication rate. 8 Although voiding dysfunction has been described as a potential complication after sling placement surgery, 10,11 it has also been suggested that some degree of bladder outlet obstruction could be related to a higher continence rate.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study for Remeex re-adjustable sling, which was conducted to the 205 patients after primary failure of MUS, revealed 71.7% of cure rates during a mean follow up of 89 months . 88 patients (42.9%) required re-adjustment (82 cases of tension increase and 6 cases of tension reduction) [46]. Compared with the standard sling, re-adjustable sling seems to result in increased success rates and decreased complications as a salvage procedure because of readjusting the inadequate tension, which could induce recurrence of incontinence or postoperative bladder outlet obstruction.…”
Section: A C C E P T E Dmentioning
confidence: 99%